Perusahaan Asuransi Dilindungi Secara Hukum Terhadap Tindakan Klaim Asuransi Yang Disalahgunakan - Yasmin Surya Rahmalia (Peneliti.net, 2023)
Property insurance has become a popular choice among the public due to its rapid growth. This type of insurance provides compensation in the event of damage to insured properties, such as houses, office buildings, and others. The purpose of this research is to analyze the forms of insurance claim abuse and the legal protection available to insurance companies in dealing with claim misuse. The research methodology used is a normative juridical approach, employing both the statute approach and the conceptual approach to address the issue. Based on the research findings, it can be concluded that the misuse of insurance claims by certain individuals in leadership positions within companies, resulting in losses in claim payments, constitutes an unlawful act regulated under Article 1365 of the Civil Code. To protect insurance companies from losses caused by claim misuse, the individuals responsible for such actions are required to reimburse the misappropriated funds to the company.